Mechanisms of Employing Secondary Event in Cinematographic Discourse: ماهر مجيد ابراهيم-شروق مالك حسن (Al-Academy, 2019)
The cinematic story depends on many construction techniques that together constitute the story features technically and the secondary events are considered one of these basic techniques that are directly affected by the employment mechanisms inside the cinematic achievement. This subject initiated the two researchers to decide the title of the research: (Mechanisms of Employing Secondary Event in Cinematographic Discourse). The research is divided into an introduction that included the problem details, the aim and defining the terms used. The first section was the act and the event in the cinematic story, which addressed the relation between the act and the event and the nature of the simulation that tries to ascend the human act and make it more organized in order to make a difference from the act and the event in life. The second section: the dramatic event structure. It addresses the importance and types of the event and its importance in the cinematography discourse. The third section: mechanisms of including the secondary events in the cinematic film which studied the importance of the secondary event compared to the main event and how to employ it inside the cinematic story. Many filmic examples have been cited concerning the mechanisms and ways of employing the secondary event. The two researchers, then, got to decide the theoretical framework indicators that would be used as tools for analyzing the sample, which is the American movie (The Perfume) directed by Tom Tucker. The two researchers came up with the results of the sample analysis in addition to the conclusions and finally a list of the references used in the research